Determination of TTX by HPLC of Horseshoe Crab Collected from Sibu Laut, Telaga Air and Pasir Putih, Muara Tebas - Mohamad Nor Fakihin Aqsa, Mohd Nor Azam (Universiti Malaysia Sarawak (UNIMAS), 2014)
In this study, the 16 sample of horseshoe crab, T. gigas and C. rotundicauda were collected from the Sibu Laut, Telaga Air and Pasir Putih, Muara Tebas. The morphological measurement (i.e body weight and carapace width) were measured by standard measuring, electronic balance and electronic scale to assess the correlation with the toxicity level. For determination of tetrodotoxin (TTX), the High Performance Liquid Chromatography was used. TTX analysis was performed by using Water 600 Cooler system by using Symmetry C18 5µm (4.6 x 150mm) column. Toxins are separated from the contaminants by a buffer solution on a reversed-phase column packed with C18 resin with an ion-pair reagent (sodium 1-heptanesulfonate; HSA). Toxins were detected by fluorescence detector (Waters 2475 Multi Fluorescence Detector) at 505 nm emission with 381 nm excitation. The sample produce a main peak, with the retention time (Rt) was compared with authentic TTX. TTX results outcome were converted to Mouse Unit (MU) in order to compare to human consumption rate. Toxicity score in the eggs of T. gigas ranged from 0.02 MU/g to 0.62 MU/g, which in the tissue from 0.03 MU/g to 1.40 MU/g. Toxicity in the eggs of C. rotundicauda ranged from 0.34 MU/g to 2.39 MU/g while in tissue ranged from 0.81 MU/g to 3.21 MU/g. Based on the Pearson Correlation coefficient for T. gigas crab is 0.399 and C. rotundicauda is 0.051. The carapace width has weak negative correlation with toxicity level of the horseshoe crab. In this study found that, Pasir Putih has higher toxicity level compared with Sibu Laut. The toxicity ranged of C. rotundicauda eggs from Sarawak was much lower compared from the Thailand, Myanmar, Bangladesh, and Vietnam. Sarawak show low level of toxicity which are 0.34-2.39 MU/g compared to the highest level of toxicity from the Vietnam 139.1 MU/g.